Faktor- Faktor Yang Mempengaruhi Tingkat Kecemasan Ibu Hamil Trimester Tiga Menjelang Persalinan - Urip Pratama; Nurul Sakdah; Rahil Okfidaria (Lembaga Pengembangan Kinerja Dosen, 2024)
Childbirth, also known as giving birth is a normal process prior pregnancy completion in women in their fertile period. Anxiety constitutes as a psychological disorder that affects childbirth process. This study aims to know the factors affecting the third trimester pregnant women’s anxiety level preceding the childbirth at Kuta Baro Public Health Center. This research designed under quantitative with analytical design, using cross sectional study method. The data collected through a questionnaire and conducted from March 6 to July 11, 2023. Population in this study was all third trimester pregnant women in Kuta Baro Public Health Center. The sample was 62 pregnant women chosen by using total sampling technique. Chi Square Test used to analyze the data. The results shows that pregnant women age with p-value 0,033, knowledge with p-value 0,088, education with p-value 0,054, and family support with p-value 0,003. In conclusion, age and family support have a significant correlation, while knowledge and education have no significant correlation to the anxiety level of third trimester pregnant women’s. This study suggests that the health officers add more programs and activities to socialize and educate the family by producing more detailed flyers and counseling on pregnancy disorders prior childbirth. Thus, the family support and their presence during the pregnancy to the childbirth process is also strongly recommended to reduce the anxiety level on pregnant women during their pregnancy.